2005
DOI: 10.1103/physrevb.71.134512
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb repulsion andTcin BCS theory of superconductivity

Abstract: Coulomb repulsion among the many electrons in a metal is in a balance, which can be toppled by even a weak electron-phonon attractive interaction. Therefore neglecting the Coulomb term from the BCS reduced Hamiltonian has little effect on T c . This is shown by a field-theoretic argument, an analysis based on the Bogoliubov model potential and a direct numerical calculation. Detailed knowledge about electrons and phonons for various materials can be incorporated into the BCS theory through a refined treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…with the N and U-processes being illustrated by the solid and dashed curved arrows in figure 1, respectively, both arrows start from k. Also consider the event arising from the second term in the brackets: which is not normalized unless h N or h U vanishes, consistent with the conclusion in [30][31][32].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…with the N and U-processes being illustrated by the solid and dashed curved arrows in figure 1, respectively, both arrows start from k. Also consider the event arising from the second term in the brackets: which is not normalized unless h N or h U vanishes, consistent with the conclusion in [30][31][32].…”
Section: Discussionsupporting
confidence: 55%
“…This is a manifestation of the algebraic contradiction within the original BCS theory [30][31][32] that the ground state electronic wavefunction cannot be normalized when normal and umklapp scattering coexist, see appendix.…”
Section: Umklapp Dilemmamentioning
confidence: 99%
“…Such a potential is known as the Bogoliubov potential. 56,57 This approximation has been used to show extremely counterintuitive behavior of the gap equation and justify a-posteriori another heavily criticized approximation of BCS, neglecting Coulomb repulsion: the BCS mechanism indeed assumes only attraction between electrons, which can be dimmed by Coulomb repulsion, but which never explicitly appears as such (like in the Bogoliubov scenario). The great result of Cooper was that binding occurs at arbitrarily small attraction.…”
Section: Bogoliubov Potentialmentioning
confidence: 98%
“…It is designed to overcome: (1) conceptual and numerical difficulties of the BCS theory and (2) uncertainty associated with l à . It is justified by its highly accurate first principles calculations for superconducting niobium, lead, [41][42][43][44][45][46][47][48] Contents lists available at ScienceDirect Physica C j o u r n a l h o m e p a g e : w w w .…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Some time ago we identified a fundamental conceptual difficulty in the Bardeen-Cooper-Schrieffer (BCS) theory of superconductivity [1,2]. Independently, in a thorough review of the theory, Hirsch concluded that it ''is fundamentally flawed'' and ''may be destined to be overhauled just as other established scientific theories of the past have been overhauled'' [3].…”
Section: Introductionmentioning
confidence: 96%